The other space of social media: Concept study of heterotopia on Instagram - Biko Nabih Fikri Zufar; Eka Kartika Sari (Jurnal Sosiologi Dialektika, 2021)
Technological developments in society are separate space into two forms, real space and virtual space. The two meet each other when either individuals or communities use virtual space. Foucault described space to be three forms: dystopia, utopia, and heterotopia. This article aims to explain Instagram as virtual space that intersects real space, forming other spaces in the process. This article uses the perspective of the sociology of space and place while also using Foucault’s theory of other space. This study used the qualitative research method with a discourse analysis approach. The finding of this article is that there are six heterotopia principles contained in Instagram’s features. The results, Instagram forms other space beyond the activity of uploading photos or videos. Instagram as a real space becomes biased because of heterotopia. Individuals interpret Instagram differently as a place to share. On the contrary, when sharing activities, other individuals may use it for more than just sharing. Instagram has changed its space due to a shift in place use. Instagram can create other spaces besides its original function of uploading photos or videos through the other features on Instagram.